Market Survey and Analysis of Packaging Information Provided by Different Pharmaceutical Companies of Bangladesh - Sarker, Shibtosh; Pal, Arindom; Sultana, Jesmin (Bangladesh Pharmaceutical Journal, 2012)
The purpose of the present study was to investigate whether or not the pharmaceutical companies of Bangladesh are providing all the necessary information and instructions in the packaging materials of pharmaceutical products which are available in Bangladesh. With this aim, the sample of secondary packaging material (cartons, labels, inserts or direction slips) of a total 150 products (from 50 generics) marketed by 15 pharmaceutical companies have been selected and were collected from different medical stores of Dhaka city. The packaging materials of the collected samples were then evaluated based on various regulatory and clinical parameters. It was found that some of the packaging materials of these selected pharmaceutical products lack several important information in terms of clinical and regulatory parameters which limits the quality of these packaging materials. DOI: http://dx.doi.org/10.3329/bpj.v15i2.12585 Bangladesh Pharmaceutical Journal 15(2): 165-169, 2012